Gains and Losses of the Mandatory Duration Regulation for Rewards Programs by Credit Cards - Sung Ick Cho; Hwaryung Lee (Korea Development Institute (KDI), 2014)
Introduced in 2010, the regulation obliging one-year duration for credit card rewards programs may have provided card companies with a cost-saving justification for terminating rewards program prematurely. In addition, the recently announced revision to the Regulation on Supervision of Credit-Specialized Financial Business prohibits card companies from altering rewards program associated with a card while the card is valid. This may have the side effect of leading card companies to offer fewer benefits and restricting consumer choices. To address this issue, it is suggested that card companies be encouraged to diversify expiration dates. - According to the survey, around 76 percent of consumers pointed to rewards programs as major consideration in opening a new credit card account. - When card companies enact a strategy regarding the duration of services, consumer responses matter most. Consumers also consider the company's policy on maintaining rewards programs when selecting credit cards. - Before the introduction of the one-year mandatory duration, the rewards programs of credit cards lasted over three years on average. This implies the mandatory duration may have been too short. - Card companies could have shortened their rewards programs duration since the one-year regulation. - When card companies decide on the duration of rewards programs, they are likely to have given serious consideration to the one-year regulation. - Card companies now can terminate rewards programs while acting in compliance with the regulation and the terms and conditions for membership, and do so without showing concern for consumers or keeping "the bona fide (good faith) principle". - It is likely that "sophisticated consumers" would sign up for fewer new cards than they may have before the regulation. The card companies have responded by reducing the duration of rewards programs. - Under the revision, consumers are left with product characterized by (fewer benefits, long duration) combination. Such a restriction of consumer choice could worsen overall consumer welfare. - Diversifying validity periods may eliminate uncertainties and restore consumer choice. Should this be encouraged, the flexibility of card companies to choose among various terms of validity could be the resolution to the welfare-loss issue.
Keywords: 330